BEST PRACTICE GUIDE TO PROCUREMENT CHALLENGES OF PUBLIC-PRIVATE PARTNERSHIPS IN INFRASTRUCTURE DEVELOPMENT IN MALAWI - Grace Namayombo SUKASUKA; David MANASE (Journal of Construction Project Management and Innovation)
Procurement of Public-Private Partnerships (PPPs) is underpinned by the project’s potential to deliver Value for Money (VfM) through risk transfer to the private sector and the existence of enabling environments. In Malawi, PPP is a relatively new concept confined to the rail services, Information Technology and Airline sectors. Its use is quite limited in infrastructure development and there is no clear understanding or perception of the required PPP enabling environments and framework arrangements to assess risk transfer and VfM which are vital in steering successful PPPs and motivate private sector investment. The aim of this paper was two-fold, thus to review PPP procurement challenges from a Malawian perspective and propose a PPP methodology framework for best practice in infrastructure development from the findings. Semi-structured telephone interviews and Inductive thematic analysis were used. Findings indicated that despite the potential for infrastructure PPPs in Malawi, the procurement process has several challenges some of which are common to the global PPP market. These include the protracted PPP procurement process of 12 to 24 months; handling of unsolicited bids; structure of the Special Purpose Vehicle; lack of robust assessment tools to ascertain VfM and risk transfer; limited capacity of  local firms in handling PPP deals; high cost of private sector finance; funding restrictions and political risk. The PPP methodology framework for best practice in Infrastructure development was proposed and documented.